Trade with China and Skill Upgrading: Evidence from Belgian Firm Level Data - Giordano Mion; Hylke Vandenbussche; Linke Zhu (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2009)
We use Belgianfirm-level data over the period 1996-2007 to analyze the impact of im- ports from China and other low-wage countries onfirm growth, exit, and skill upgrading in manufacturing. For this purpose we use both industry-level andfirm-level imports by country of origin and distinguish betweenfirm-level outsourcing of nal versus intfirmediate goods. Results indicate that, both industry-level import competition andfirm-level outsourcing to China reducefirm employment growth and induce skill upgrading. In contrast, industry-level imports have no e ect on Belgianfirm survival, whilefirm-level outsourcing of nished goods to China even increasedfirm's probability of survival. In tfirms of skill upgrading, the e ect of Chinese imports is large. Industry import competition from China accounts for 42% of the withinfirm increase in the share of skilled workers in Belgian manufacturing over the period of our analysis, but this e ect, as well as the employment reducing e ect, remains mainly in low- tech industries. firm-level outsourcing to China further accounts for a small but signi cant increase in the share of non-production workers. This change in employment structure is in line with predictions of o shoring models and Schott's (2008) 'moving up the quality ladder' story. All these results are robust to IV estimation.
Keywords: F11; F14; F16; 330; import competition; outsourcing; China; skill upgrading; Internationaler Wettbewerb; Import; Outsourcing; Unternehmenserfolg; Humankapital; Qualifikation; Industrie; Belgien; China